Ensuring organisational and legal conditions for financing the social sector of Ukraine - S. M. Bortnyk; I. O. Sievidova (Law and Safety)
The legal aspects of regulation of budgetary financing of social services have been analysed, and the main directions of improving the efficiency of the system of budgetary financing of social protection and social security of the population of Ukraine in modern conditions have been identified. Based on the analysis of scientific views, theoretical approaches to building a budget system in the context of social protection have been considered. The shortcomings of legal regulation of mechanisms for financing the provision of social protection services have been identified, and the main factors for improving the efficiency of budget financing and the inclusiveness of social protection have been described.